Sexting Trends Among Makassar Adolescents - Ridwan, Budiawan; Dengen, Alvianus (representamen, 2025)
The development of technology and digital communication has transformed social interactions among adolescents, particularly through sexting behavior, defined as the sending and receiving of sexually explicit messages, images, or videos via electronic devices. This study aims to explore sexting trends among adolescents in Makassar City. The research method employed is a survey, systematically collecting data from a representative sample of adolescents aged 12 to 18 attending various junior high and high schools. The results indicate that sexting behavior is relatively common among adolescents, with factors such as peer influence and access to social media significantly contributing to its prevalence. The conclusion emphasizes the importance of education and policy implementation in schools to address sexting issues, as well as the need for effective prevention programs. The contribution of this research lies in providing a better understanding of sexting behavior among adolescents and offering recommendations for interventions that can be undertaken by educators and parents. Keywords: Sexting; Adolescents; Digital Communication; Social Media; Prevention Strategies